Novel navigation signal design based on spreading code time shift position modulation - Jiafang KANG; Hongxing WANG; Xiguo LIU; Peilin ZHONG; Bifeng LI (Tongxin xuebao)
A novel navigation signal design method based on spread code time shift position modulation was proposed,which inherits the idea of separating the pilot signal component and the data signal component,and applies time shift position of the spread code to carry data information.The old pattern of using carrier phase to carry information was changed,the power efficiency of data signal components and the performances of the satellite navigation system were improved.Theoretical analysis and simulation results show that the proposed method can significantly improve the transmission rate of data signal component or power ratio of the pilot signal component to data signal component without increasing the total transmission power.Then,the transmission rate,acquisition and tracking performance,positioning accuracy and other technical indicators of the satellite navigation system can be further improved.